2017
DOI: 10.1017/jfm.2017.346
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic resonance in the potential core of subsonic jets

Abstract: The purpose of this paper is to characterize and model waves that are observed within the potential core of subsonic jets and relate them to previously observed tones in the near-nozzle region. The waves are detected in data from a large-eddy simulation of a Mach 0.9 isothermal jet and modelled using parallel and weakly non-parallel linear modal analysis of the Euler equations linearized about the turbulent mean flow, as well as simplified models based on a cylindrical vortex sheet and the acoustic modes of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
243
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 168 publications
(271 citation statements)
references
References 50 publications
27
243
1
Order By: Relevance
“…This decomposition method identifies energy-ranked modes where each oscillates at a single frequency, and has been overlooked since its inception despite its benefits over the common spatial form of POD [43] and dynamic mode decomposition [16]. There are few techniques in the literature for computing SPOD modes [13,44,45]. In this study, we used the procedure developed by Towne et al [13], as it was found to be computationally more efficient compared to others.…”
Section: Spectral Proper Orthogonal Decomposition (Spod)mentioning
confidence: 99%
See 4 more Smart Citations
“…This decomposition method identifies energy-ranked modes where each oscillates at a single frequency, and has been overlooked since its inception despite its benefits over the common spatial form of POD [43] and dynamic mode decomposition [16]. There are few techniques in the literature for computing SPOD modes [13,44,45]. In this study, we used the procedure developed by Towne et al [13], as it was found to be computationally more efficient compared to others.…”
Section: Spectral Proper Orthogonal Decomposition (Spod)mentioning
confidence: 99%
“…There are few techniques in the literature for computing SPOD modes [13,44,45]. In this study, we used the procedure developed by Towne et al [13], as it was found to be computationally more efficient compared to others. The details of the procedure can be found in the comprehensive paper by Towne et al [13].…”
Section: Spectral Proper Orthogonal Decomposition (Spod)mentioning
confidence: 99%
See 3 more Smart Citations